2020
DOI: 10.1248/bpb.b20-00258
|View full text |Cite
|
Sign up to set email alerts
|

Galangin Reverses Hepatic Fibrosis by Inducing HSCs Apoptosis <i>via</i> the PI3K/Akt, Bax/Bcl-2, and Wnt/β-Catenin Pathway in LX-2 Cells

Abstract: Hepatic fibrosis (HF) is a common disease, with currently no available treatment.Galangin, a natural flavonoid extracted from Alpinia officinaruim Hance, has multiple effects demonstrated in previous studies. The aim of the present study was to explore the anti-fibrogenic effect of galangin in vitro, and research its potential molecular mechanisms. LX-2 cells were chosen as an in vitro HF model, and were treated with galangin in different concentrations. Cell viability was analyzed using Cell Counting Kit-8 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…Galangin is an extract of the ginger plant galangal, in which the main chemical component is 3,5,7-trihydroxyflavone, a polyphenolic compound. 2 Previous studies have shown that galangin has the ability to inhibit cell proliferation, 3 promote apoptosis, 4 inhibit cell metastasis, 5 and induce cell autophagy 6 as well as provide anti-inflammatory 7 and antioxidant effects. 8 In terms of mechanisms, galangin has reversed liver fibrosis by inhibiting the activation of the PI3K/AKT signaling pathway; 4 galangin has also alleviated rheumatoid arthritis by inhibiting the activation of the PI3K/AKT signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galangin is an extract of the ginger plant galangal, in which the main chemical component is 3,5,7-trihydroxyflavone, a polyphenolic compound. 2 Previous studies have shown that galangin has the ability to inhibit cell proliferation, 3 promote apoptosis, 4 inhibit cell metastasis, 5 and induce cell autophagy 6 as well as provide anti-inflammatory 7 and antioxidant effects. 8 In terms of mechanisms, galangin has reversed liver fibrosis by inhibiting the activation of the PI3K/AKT signaling pathway; 4 galangin has also alleviated rheumatoid arthritis by inhibiting the activation of the PI3K/AKT signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…2 Previous studies have shown that galangin has the ability to inhibit cell proliferation, 3 promote apoptosis, 4 inhibit cell metastasis, 5 and induce cell autophagy 6 as well as provide anti-inflammatory 7 and antioxidant effects. 8 In terms of mechanisms, galangin has reversed liver fibrosis by inhibiting the activation of the PI3K/AKT signaling pathway; 4 galangin has also alleviated rheumatoid arthritis by inhibiting the activation of the PI3K/AKT signaling pathway. 9 The PI3K/AKT signaling pathway plays an important role in the process of neointimal hyperplasia after vascular injury.…”
Section: Introductionmentioning
confidence: 99%
“…47,48 Based on our previous study, GA is highly effective against HF, as the inhibition of aHSC in vitro was initiated at the concentration of 6 mg mL −1 . 24 The capacity of GA-NPs and RA-GA-NPs was approximately 240 mg. This capacity could meet the requirement for drug administration and avoid toxicity induced by an overdose.…”
Section: Characterization Of Npsmentioning
confidence: 99%
“…22,23 Our earlier studies also revealed that GA shows anti-brotic activity in LX-2 cells by inhibiting the PI3K/Akt pathway and its downstream pathways. 24 However, aer oral administration, GA exhibits low bioavailability due to its water-soluble hydrophobicity; this limits its clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Inhibition of HSCs through induction of autophagy and natural killer cell-mediated killing: Dihydromyricetin (DHM) [228] . (4) Reverse LF by inducing HSC apoptosis through Wnt/β-linked protein, Bax/Bcl-2 as well as PI3K/Akt pathways: Galangin [229] . (5) Inhibiting HSC activation by targeting the miR-181b/PTEN axis: Liquiritigenin (LQ) [230] .…”
Section: Othersmentioning
confidence: 99%